ANALYSIS OF VACCINATION RATES AND IMMUNIZATION COVERAGE OF CHILDREN WHOSE MOTHERS HAD SARS COV-2 DURING PREGNANCY - Яковлева, Людмила Викторовна; Шангареева, Гузель Наилевна; Мулюкова, Азалия Ирековна; Николаева, Айгуль Фаргатовна; Бобрик, Дарья Владимировна (Mother and Baby in Kuzbass, 2023)
The aim of the research – the study of vaccination according to the national vaccination calendar of children born to mothers who had SARS CoV-2 during pregnancy, correlating the time of detection of COVID-19.Materials and methods. The paper presents an analysis of 46 preventive vaccination cards (form 063/y) and preventive vaccination sheets in the child development card (form 25/y) in the period from 2021 to 2022 on the basis of the State Budgetary Institution of Health of the Republic of Bashkortostanof the State Clinical Hospital of the Demsky District of Ufa, the Republic of Bashkortostan on timely immunization children whose mothers had SARS CoV-2 during pregnancy. The assessment of immunization was carried out according to the parameters: no vaccination, incomplete vaccination and complete vaccination, in accordance with the age of the child and the timing of vaccination according to the national calendar.Results. Studies have shown that for the period from 2021 to 2022 there were deviations in the timing of immunization of the national vaccination schedule.Conclusion. A comparative analysis of the immunization of children during the pandemic from 2021 to 2022 on the basis of the State Budgetary Institution of Health of the Republic of Belarus of the State Clinical Hospital of the Demsky District of Ufa showed that due to the regimen of anti-epidemiological measures and the age of the subjects, the vaccination rate and immunization coverage of children were at a low level. The highest rates of childhood immunization were achieved against tuberculosis. The lowest indicator was in the level of vaccination of children against hepatitis B and pneumococcal infection.
Keywords: vaccination calendar; vaccine-preventable infections; newborns; COVID-19; mother